Analysis of The Impact of Corporate Governance On Profitability and Firm Value During The Covid-19 Pandemic - Made Reina Candradewi; Henny Rahyuda (Quantitative Economics and Management Studies, 2023)
This study aims to analyze the effect of Independent Commissioner s, managerial ownership and audit committees on profitability and firm value in the Indonesian capital market, namely manufacturing companies on the Indonesia Stock Exchange (IDX). This research is expected to provide insight and enrich scientific knowledge about the relationship between corporate governance to profitability and company value, especially during the Covid-19 pandemic. This research was conducted using a quantitative approach. The sampling technique used in this research is purposive sampling method. The companies included in the sample of this study are manufacturing companies that are always listed on the IDX from 2020 to 2021. The total sample in this study is 60 companies. Based on the results of the regression analysis and mediation test, it can be concluded that the variables of Independent Commissioner s, managerial ownership, audit committees have no significant effect on profitability and firm value. Profitability is not able to mediate the relationship between Independent Commissioner s, managerial ownership and audit committee on firm value. However, profitability has a positive and significant effect on firm value.